DESCRIPTION OF WOMEN'S ORGANIZATIONAL MANAGEMENT IN THE PREVENTION OF MATERNAL AND CHILD DEATH - Ibnu Hajar; Habibi; Andi Bukti Djufri; Muhammad Amri; Nildawati (Homes Journal = Hospital Management Studies Journal, 2023)
Backgrounds: The maternal mortality rate (MMR) and the infant and under-five mortality rate (IMR and AKABA) are indicators that show the welfare and health of the people in a country. Objective: This study aims to conduct a study related to the description of the management of women's organizations in preventing maternal and child deaths. Method: The method used is descriptive qualitative, with informants being women's organizations with maternal and child health programs. Result: Women's organizations play a role in reducing maternal and child mortality by conducting active counseling, active assistance, educating the community and carrying out activities that support maternal and child health. Conclusion: The involvement of women's organizations in the planning and implementation of programs to reduce maternal and child mortality needs continuous efforts and assistance so that the programs run effectively and there is an increase in the knowledge and understanding of mass organizations related to gender and women's health and maternal and child health.